2010
DOI: 10.1016/j.dld.2009.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Practice guidelines for the treatment of hepatitis C: Recommendations from an AISF/SIMIT/SIMAST Expert Opinion Meeting

Abstract: a b s t r a c tIt is increasingly clear that a tailored therapeutic approach to patients with hepatitis C virus infection is needed. Success rates in difficult to treat and low-responsive hepatitis C virus patients are not completely satisfactory, and there is the need to optimise treatment duration and intensity in patients with the highest likelihood of response. In addition, the management of special patient categories originally excluded from phase III registration trials needs to be critically re-evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(11 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…Besides the CB2-63 QQ variant, the multivariate analysis identified another three factors independently associated with the PNALT status: HCV genotype 2, an older age and a lower BMI. HCV genotype 2 and a lower BMI have been suggested as independent predictors of PNALT in previous studies [10], [30], [31], and confirmed in the present investigation. Instead, this is the first time the CB2-63 QQ variant and an older age have been cited as independent predictors of the PNALT status.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Besides the CB2-63 QQ variant, the multivariate analysis identified another three factors independently associated with the PNALT status: HCV genotype 2, an older age and a lower BMI. HCV genotype 2 and a lower BMI have been suggested as independent predictors of PNALT in previous studies [10], [30], [31], and confirmed in the present investigation. Instead, this is the first time the CB2-63 QQ variant and an older age have been cited as independent predictors of the PNALT status.…”
Section: Discussionsupporting
confidence: 89%
“…Some individuals show a mild indolent clinical course for decades, others rapidly progress to end-stage liver disease [9], whereas about 20–30% of cases remain asymptomatic with normal serum alanine aminotransferase (ALT) levels lifelong. According to the Italian guidelines, the definition of an anti-HCV carrier with persistently normal ALT (PNALT) serum values applies to a subject with at least 9 consecutive ALT normal values observed at two-monthly intervals over an 18-month observation period[10]and identifies a subclinical form of CHC. The majority of carriers with PNALT show histological evidence of necroinflammation and fibrosis, but the liver lesions are clearly less severe than those observed in subjects with abnormal ALT [11], [12].…”
Section: Introductionmentioning
confidence: 99%
“…Of the 475 enrolled patients, 83 (17.4%) were HCV carriers with persistently normal alanine-aminotransferase serum values (PNALT) and 392 (82.6%) had a history of steadily abnormal serum ALT values. According to the Italian guidelines [28], the definition of an anti-HCV carrier with PNALT serum values applies to a subject with at least 9 consecutive ALT normal values observed at 2-monthly intervals over an 18-month observation period, while the definition of chronic hepatitis C to a subject with abnormal ALT values in absence of other causes. A complete history with possible route of infection and standard biochemical liver function tests were collected.…”
Section: Methodsmentioning
confidence: 99%
“…Genotypes 2 and 3 are recognized less frequently among CHC patients from the KSA (5, 11). The current standard treatment for CHC is the combination of pegylated interferon (PEG-INF) and ribavirin for 48 weeks for genotypes 1 and 4, and 24 weeks for genotypes 2 and 3 (7, 8, 12-14). This treatment is effective in up to 70-95% of patients with genotypes 2 and 3, 44-54% of patients with genotype 1, and 58-86% of patients with genotype 4 (7, 8, 12, 14-17).…”
Section: Introductionmentioning
confidence: 99%